Betwixt and Between: A Narrative Inquiry into EFL Pre-Service Teachers’ Identity Negotiation and Borrowed Agency in Vietnam - Hoai Thi Thu Nguyen; Hue Thi Trinh Tran (WISE Pendidikan Indonesia, 2026)
This qualitative narrative inquiry examined how three Vietnamese EFL pre-service teachers negotiated professional identity during an eight-week teaching practicum. Three final-year students were purposively selected from twelve eligible candidates to represent varied linguistic and educational backgrounds. Data comprised nine semi-structured interviews, twenty-four weekly narrative frames, and participant-selected artifacts, interpreted through Clandinin and Connelly’s three-dimensional narrative space. Chronological restorying followed by cross-case analysis revealed that the practicum operated as a liminal environment in which professional agency was provisional and mentor-dependent. Lan and Vy strategically complied with mentor expectations when communicative or technology-mediated pedagogies conflicted with exam-oriented routines and hierarchical evaluation. By contrast, Minh experienced the same structure as a protective scaffold that reduced anxiety about linguistic legitimacy and validated his grammar-focused identity. The findings refine the concept of borrowed agency by showing that constrained autonomy is not experienced uniformly; its meaning depends on trainees’ prior pedagogical orientation and linguistic confidence. In comparable EFL teacher-education contexts, structured mentor training, dialogic co-planning, and protected low-stakes experimentation may support identity development without making pedagogical conformity the primary route to practicum success.